The Combined Performance of ADC, CSF CXC Chemokine Ligand 13, and CSF Interleukin 10 in the Diagnosis of Central Nervous System Lymphoma - Mabray, M.C.; Barajas, R.F.; Villanueva-Meyer, J.E.; Zhang, C.A.; Valles, F.E.; Rubenstein, J.L.; Cha, S. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: CXC chemokine ligand 13 and interleukin 10 have emerged as CSF biomarkers for the diagnosis of CNS lymphoma. Our hypothesis is that the combined use of ADC, CXC chemokine ligand 13, and interleukin 10 will result in increased diagnostic performance compared with the use of ADC values alone.MATERIALS AND METHODS: Eighty-seven patients were included in this study, including 43 with CNS lymphoma and 44 without CNS lymphoma (21 metastases, 14 high-grade gliomas, 9 tumefactive demyelinating lesions) who had undergone CSF proteomic analysis and had a new enhancing mass on brain MR imaging. Average ADC was derived by contouring the contrast-enhancing tumor volume. Group means were compared via t tests for average ADC, CXC chemokine ligand 13, and interleukin 10. Receiver operating characteristic analysis was performed for each individual variable. Multiple-variable logistic regression with receiver operating characteristic analysis was performed, and the multiple-variable receiver operating characteristic was compared with single-variable receiver operating characteristics.RESULTS: The average ADC was lower and CSF CXC chemokine ligand 13 and interleukin 10 values were higher in CNS lymphoma (P < .001). Areas under the curve ranged from 0.739 to 0.832 for single-variable ROC. Multiple-variable logistic regression yielded statistically significant individual effects for all 3 variables in a combined model. Multiple-variable receiver operating characteristics (area under the curve, 0.928) demonstrated statistically significantly superior diagnostic performance compared with the use of single variables alone.CONCLUSIONS: The combined use of ADC, CSF CXC chemokine ligand 13, and interleukin 10 results in increased diagnostic performance for the diagnosis of CNS lymphoma. This finding highlights the importance of CSF analysis when the diagnosis of CNS lymphoma is considered on the basis of MR imaging.ADCavgaverage ADCCNSLcentral nervous system lymphomaCXCL-13CXC chemokine ligand 13IL-10interleukin 10ROCreceiver operating characteristicAUCarea under the curve